HUBUNGAN POLA KONSUMSI GLUTEN DAN KASEIN, KEPATUHAN DIET GLUTEN FREE CASEIN FREE (GFCF) DENGAN PERILAKU AUTIS DI RUMAH AUTIS BEKASI - Wahyu Permata Sri Tunggal Djati; Ahmad Faridi; Nur Setiawati Rahayu (UHAMKA PRESS, 2017)
The prevalence of autism children is increasing, around 2013, it is estimated that peoplewith autism in the world reach 1 per 160 children or around 0.3%. There are two types ofprotein that need to be avoided by children with autism, namely gluten and casein. Thegeneral objective of this study was to determine the relationship between gluten and caseinconsumption patterns, compliance of the Gluten Free Casein Free (GFCF) diet with autisticbehavior in Autism Home, Bekasi. The subject of the study was autism children at the BekasiAutism House, which numbered 25 children. The study was conducted using a cross sectionaldesign. Data collection on gluten and casein consumption patterns and GFCF dietarycompliance using Food Frequency Questionnaire (FFQ), while data on autistic behavior werecollected using the CARS2-ST ST (Childhood Autism Rating Scale 2 – Standard Version) questionnaire. The results showed that more than half the number of samples had a rare pattern of consumption of gluten and casein. As many as 88% of the samples did not adhereto the GFCF diet and 76% of the samples had severe autistic behavior. The chi-square testresults showed that there was a correlation between gluten consumption patterns and GFCFdiet compliance with autism behavior (p-value <0.05).